Capital flows, EU integration and the global financial crisis: An empirical analysis - Ahmet Ihsan Kaya; Jakob de Haan (Journal of Applied Economics, 2022)
We investigate the impact of European Union (EU) integration on capital flows to prospective new EU member states. Using annual data between 1992 and 2020, our results suggest that although EU integration increased net capital flows before the Global Financial Crisis (GFC), it was not able to shield countries from the general decline in capital flows that occurred after the GFC. Furthermore, the results show that the impact of EU integration mainly runs through improved institutional quality. We also find considerable heterogeneity in the drivers of different types of capital flows (FDI, portfolio investments, and other capital flows) that we consider.
Keywords: C33; F21; F36; 330; Capital flows; European Union integration; fixed effects panel data model; global financial crisis